2008
DOI: 10.1103/physrevb.78.085314
|View full text |Cite
|
Sign up to set email alerts
|

Voltage control of magnetocrystalline anisotropy in ferromagnetic-semiconductor-piezoelectric hybrid structures

Abstract: We demonstrate dynamic voltage control of the magnetic anisotropy of a (Ga,Mn)As device bonded to a piezoelectric transducer. The application of a uniaxial strain leads to a large reorientation of the magnetic easy axis which is detected by measuring longitudinal and transverse anisotropic magnetoresistance coefficients. Calculations based on the mean-field kinetic-exchange model of (Ga,Mn)As provide microscopic understanding of the measured effect. Electrically induced magnetization switching and detection of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
98
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 30 publications
1
98
0
Order By: Relevance
“…Their ferromagnetic resonance measurements indicated that whilst the free-energy density for magnetizing the film along the in-plane ⟨100⟩ directions were equivalent, due to the anticipated cubic magnetocrystalline anisotropy in their Fe films, the in-plane ⟨110⟩ directions were inequivalent -indicative of an additional uniaxial magnetic anisotropy term K U with easy-axis oriented along the [110] and hard-axis along the [110] direction. The origin of this uniaxial magnetic anisotropy which is found in these, and related, films has escaped explanation: it is toward gaining an understanding of this anisotropy we will focus the remainder of this review.…”
Section: Cubic Anisotropy In a Ferromagnetic Metalmentioning
confidence: 99%
See 4 more Smart Citations
“…Their ferromagnetic resonance measurements indicated that whilst the free-energy density for magnetizing the film along the in-plane ⟨100⟩ directions were equivalent, due to the anticipated cubic magnetocrystalline anisotropy in their Fe films, the in-plane ⟨110⟩ directions were inequivalent -indicative of an additional uniaxial magnetic anisotropy term K U with easy-axis oriented along the [110] and hard-axis along the [110] direction. The origin of this uniaxial magnetic anisotropy which is found in these, and related, films has escaped explanation: it is toward gaining an understanding of this anisotropy we will focus the remainder of this review.…”
Section: Cubic Anisotropy In a Ferromagnetic Metalmentioning
confidence: 99%
“…It is obvious that care must be taken in applying the correct expression: further difficulties may arise when the interfacial uniaxial easy axis is no-longer oriented along the [110] direction, but rather along [110], as is the case in films deposited on, for example, InAs(001). When considering such an admixture of cubic magnetocrystalline and interfacial uniaxial magnetic anisotropies, three distinct situations may occur: i) when the ferromagnetic film is very thick, in which case |K eff U | ≪ |K eff 1 |, the uniaxial anisotropy is negligible and the film behaves as if it has only cubic in-plane magnetic anisotropy; ii) in the case when the ferromagnetic film is very thin, in which case |K eff U | ≫ |K eff 1 |, the cubic anisotropy is negligible and the film behaves as if it has only uniaxial in-plane magnetic anisotropy; and, iii) when the film is of a thickness where |K eff U | ≈ |K eff 1 |, both terms contribute, which results in two-stage magnetization reversal for fields applied along the uniaxial hard-axis (UHA), depicted schematically in the inset to the lower right frame of figure 2.…”
Section: Mixed Cubic and Uniaxial Magnetic Anisotropymentioning
confidence: 99%
See 3 more Smart Citations